Developing climate governance strategies in Nigeria: An emphasis on methane emissions mitigation - Onwusameka Sonny Ogbowuokara; Tambari Gladson Leton; John Nwenearizi Ugbebor; Ochuko Felix Orikpete (The Journal of Engineering and Exact Sciences)
In the face of escalating global climate change concerns, nations, including Nigeria, are urged to enhance their climate governance strategies. Nigeria, a key player in Africa and particularly susceptible to climate change, confronts the critical task of addressing and mitigating its greenhouse gas emissions, with a significant focus on methane. This study explores the evolution of Nigeria's climate governance, emphasizing methane emission mitigation. It examines Nigeria's varied emission sources across agriculture, fossil fuel industries, and waste management, underscoring the necessity for sector-specific strategies. The research outlines the methods for identifying emissions, the collaborative efforts with stakeholders, and the resultant action plans. It highlights the pivotal role of the Climate and Clean Air Program (CCAP) and its compliance with the National Climate Change Policy and Response Strategy (NCCPRS) and the Paris Agreement. The paper also stresses the importance of integrating scientific inquiry with practical governance, exploring the benefits of synergistic collaborations. However, it acknowledges the challenges in aligning diverse stakeholder interests. The study reveals Nigeria's proactive and holistic approach to climate governance, particularly concerning methane emissions. It emphasizes that effective climate action requires a blend of policy development, scientific accuracy, and inter-sectoral cooperation. Nigeria's experience offers valuable lessons for other countries in implementing customized climate initiatives, highlighting both the opportunities and complexities involved.